Improvement of the taxation system of the Grand Duchy of Lithuania peasants in the 16th century - Kozhar, Alena V. (Journal of the Belarusian State University. Law, 2022)
The author analyses the taxation system of the Grand Duchy of Lithuania and its evolution at the beginning of the 16th century. The relevance of this topic is due to the lack of scientific research on the history of the development of the tax system, without which it is impossible to form an effective taxation system at the present stage. As a result of the conducted research, the author comes to the conclusion that the peculiarities of territorial formation of the Grand Duchy of Lithuania caused the existence of significant quantity of various taxes and duties in the state, and if initially they were collected from the entire population, then later the class principle was introduced and the burden of taxation fell mainly on ordinary people, peasants and burghers. Trends in the development of taxation were also identified, namely, the replacement of various local taxes with non-national ones, the replacement of food taxes with monetary taxes, an increase in the number of indirect taxes and the emergence of extraordinary ones.
Keywords: taxation; peasants; direct taxes; polyudye; staciya; mezlivo; tribute; indirect taxes; emergency taxes